Developing Interactive Teaching Materials using Nearpod to Strengthen Students’ Mathematical Literacy - Septy Sari Yukans; Rahma Siska Utari; Dea Alvionita Azka; Dinda Audina Rahmah (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
The low achievement of Indonesian students in international assessments such as the Programme for International Student Assessment (PISA) highlights the need for contextual and technology-based innovations in mathematics learning. This study aims to develop Nearpod-based interactive teaching materials that are valid, practical, and have a potential effect in strengthening junior high school students’ mathematical literacy. The research employed a formative evaluation approach consisting of the stages of preliminary study, self-evaluation, expert review, one-to-one, small group, and field test. The participants were 31 eighth-grade students from MTsN 1 Ogan Ilir, South Sumatra. Data were collected through walkthroughs, interviews, observations, and questionnaires, and analyzed using a qualitative descriptive method. The findings revealed that the developed teaching materials were valid in terms of content, construct, and language; practical for classroom implementation; and demonstrated a potential effect in enhancing students’ mathematical literacy through active engagement in the Formulate, Employ, and Interpret processes as outlined in the PISA 2022 framework. This result from students’ post-test work, which showed improved accuracy in modeling and interpreting the contextual problem. This study contributes a structured and literacy-oriented model for developing technology-based interactive teaching materials, which can serve as a reference for mathematics learning innovation in the 21st century.